A novel biocompatible antibacterial product: Nanoliposomes loaded with poly(hexamethylene biguanide chloride). (May 2017) - Ahani, Elnaz; Montazer, Majid; Toliyat, Tayebeh; Mahmoudi Rad, Mahnaz
In this study, nanoliposome-loaded poly(hexamethylene biguanide) is introduced as a novel biocompatible antibacterial product with higher activity than microliposomes. Soy lecithin as a clean product was used to prepare various nanoliposomes through sonication, high-pressure homogenizer, and normal homogenizer and also microliposomes through two methods of lipid film hydration and incubation methods. The nanoliposomes were formed under sonication with the size of 50 nm. The prepared liposomes were then loaded with poly(hexamethylene biguanide chloride) and the inclusion percentage was measured. The release profile of liposomes in buffer showed a release of 92% for poly(hexamethylene biguanide) during 24 h. The loaded liposomes were characterized with particle size analyzer, nuclear magnetic resonance, X-ray diffraction, Fourier transform infrared spectroscopy, and scanning electron microscopy. The antibacterial properties of different micro and nanoliposomes were investigated against a Gram-negative ( Escherichia coli ) and a Gram-positive ( Staphylococcus aureus ) bacteria. The poly(hexamethylene biguanide)–loaded nanoliposomes indicated higher antibacterial activities than microliposomes. Nanoliposomes have the potential to entrap lower poly(hexamethylene biguanide) dosages while retaining optimum therapeutic efficacy in the target site having lower cytotoxicity with lower side effects. The cytotoxicity of poly(hexamethylene biguanide) entrapped in liposomes was studied in human dermal fibroblasts and compared with free poly(hexamethylene biguanide) and blank liposomes. The maximum cytotoxicity was observed for free poly(hexamethylene biguanide) that is substantially decreased through loading within liposomes structure. Overall, the encapsulation of poly(hexamethylene biguanide) in liposomes improved the biocompatibility and safety of the product introducing a useful biocompatible antibacterial polymer for treatments of infectious diseases.